2004
DOI: 10.1007/s00213-004-2034-0
|View full text |Cite
|
Sign up to set email alerts
|

Mapping dopamine D2/D3 receptor function using pharmacological magnetic resonance imaging

Abstract: These results suggest that phMRI may potentially prove useful to map DAR function non-invasively in multiple brain regions simultaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
102
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(113 citation statements)
references
References 55 publications
11
102
0
Order By: Relevance
“…This pair of data showed that rats with no needle insertion do not differ from rats with needles inserted but without current passing in terms of rCBV time courses ( figure 1A). The time courses and rCBV maps from the whole AMPH-only group were similar to those published previously [5] .…”
Section: The Insertion Of Ea Needles Alone Did Not Cause the Rcbv Chasupporting
confidence: 83%
See 2 more Smart Citations
“…This pair of data showed that rats with no needle insertion do not differ from rats with needles inserted but without current passing in terms of rCBV time courses ( figure 1A). The time courses and rCBV maps from the whole AMPH-only group were similar to those published previously [5] .…”
Section: The Insertion Of Ea Needles Alone Did Not Cause the Rcbv Chasupporting
confidence: 83%
“…Preparation for microdialysis in the striatum were carried out as previously described [5] with the coordinate for the dialysate probe at [AP −0.26; ML 4.4; DV 7.0] [26]. Dialysate samples were acquired in 10 min time intervals.…”
Section: Microdialysismentioning
confidence: 99%
See 1 more Smart Citation
“…Other efforts to decode the neurovascular coupling between dopamine receptor function and a concomitant hemodynamic change provide a solid basis for the interpretation of dopaminergically related signal. fMRI with drug challenges has consistently shown that D1-like agonism is associated with increased hemodynamics changes, while D2-like agonism is associated with negative hemodynamic changes 100103 . Data further show that hemodynamic changes (measured using either BOLD or CBV) are strongly correlated with dopamine release measured using microdialysis at high dopamine levels, and are mediated for opposing changes at low dopamine release levels due to the higher affinity of D2 over D1 receptors 104108 .…”
Section: Multi-modal Imaging Of Receptor Functional Dynamics Witmentioning
confidence: 99%
“…fMRI with drug challenges has consistently shown that D1-like agonism is associated with increased hemodynamics changes, while D2-like agonism is associated with negative hemodynamic changes 100103 . Data further show that hemodynamic changes (measured using either BOLD or CBV) are strongly correlated with dopamine release measured using microdialysis at high dopamine levels, and are mediated for opposing changes at low dopamine release levels due to the higher affinity of D2 over D1 receptors 104108 . Together, these animal data are surprisingly robust, with numerous studies across different dopamine antagonists and agonists of specific sub-types showing no exceptions to the coupling rules of D1/D5 yielding positive changes and D2/D3 yielding negative changes 11 .…”
Section: Multi-modal Imaging Of Receptor Functional Dynamics Witmentioning
confidence: 99%